164k views
3 votes
E Solve for x 6(x - 1) = 9(x + 2) x = -8 x= 3 x = 8​

User Rbaldwin
by
5.7k points

2 Answers

2 votes

Answer:

Explanation:

6x - 6 = 9x + 18

-3x - 6 = 18

-3x = 24

x = -8 is the solution

User Dirleyrls
by
4.6k points
2 votes

Answer:

x = -8

Explanation:


6(x - 1) = 9(x + 2)

Expand :


6(x - 1) = 6x - 6 \\ 9(x + 2) = 9x + 18


6x - 6 = 9x + 18

Collect like terms and simplify


6x - 9x = 18 + 6 \\ - 3x = 24

Divide both sides of the equation by -3


( - 3x)/( - 3) = (24)/( - 3) \\ x = - 8

User Ioquatix
by
4.6k points